2022
DOI: 10.1590/2317-6431-2022-2698en
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing and feeding outcomes associated with orotracheal intubation and tracheostomy in pediatrics

Abstract: Purpose To verify the swallowing and feeding outcomes of pediatric patients undergoing prolonged OTI, considering those who progressed to tracheostomy afterward. Methods Retrospective cohort study, carried out by analyzing the medical records of patients admitted to the Pediatric ICU and followed up until hospital discharge, between 03/2017 and 12/2018. Results Of the 51 patients included, 64.7% were male and the median age 6.7 months. Patients undergoing OTI for a median of 7 days had mild dysphagia and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
0
0
1
Order By: Relevance
“…A tracheostomy is an invasive procedure that guarantees ventilation in cases where the airway is compromised or due to the need for prolonged mechanical ventilation 1 . International literature reports that 0.5 to 2% of children submitted to intubation and mechanical ventilation in intensive care units require tracheostomy 2 . A study that addresses the epidemiology of pediatric tracheostomy indicated that 24.8% of the causes were cardiorespiratory, 28.7% neurological, and 46.5% due to anatomical airway obstruction 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tracheostomy is an invasive procedure that guarantees ventilation in cases where the airway is compromised or due to the need for prolonged mechanical ventilation 1 . International literature reports that 0.5 to 2% of children submitted to intubation and mechanical ventilation in intensive care units require tracheostomy 2 . A study that addresses the epidemiology of pediatric tracheostomy indicated that 24.8% of the causes were cardiorespiratory, 28.7% neurological, and 46.5% due to anatomical airway obstruction 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The care of children using a tracheostomy is addressed in discussions and consensus among professionals who serve this population. 2017 the Clinical Consensus of National Recommendations in Tracheostomized Children from the Brazilian Academy of Pediatric Otorhinolaryngology (ABOpe) and the Brazilian Society of Pediatrics (SBP) was published 2 . However, the invisibility of the nurses' participation in preparing this document, a key actor during hospitalization and preparation for hospital discharge, was noted.…”
Section: Introductionmentioning
confidence: 99%
“…La traqueostomía es un procedimiento invasivo que asegura la ventilación en los casos en que la vía aérea está comprometida o debido a la necesidad de ventilación mecánica prolongada 1 . La literatura internacional informa de que entre el 0,5% y el 2% de los niños sometidos a intubación y ventilación mecánica en unidades de cuidados intensivos requieren una traqueostomía 2 . Un estudio sobre la epidemiología de la traqueotomía pediátrica indicó que el 24,8% de las causas eran cardiorrespiratorias, el 28,7% neurológicas y el 46,5% debido a obstrucción anatómica de las vías aéreas 3 .…”
Section: Introductionunclassified
“…El cuidado de los niños que utilizan traqueostomías es discutido y consensuado por los profesionales que atienden a esta población. En 2017, la Academia Brasileira de Otorrinolaringologia Pediátrica (ABOPe) y la Sociedade Brasileira de Pediatria (SBP) publicaron un Consenso Clínico de Recomendaciones Nacionales para Niños Traqueostomizados 2 . Sin embargo, constatamos la invisibilidad de la participación de los enfermeros en la elaboración de este documento, actor clave durante la hospitalización y la preparación del alta.…”
Section: Introductionunclassified
“…O cuidado da criança em uso de traqueostomia é abordado em discussões e consensos entre profissionais que atendem a essa população. Em 2017, foi publicado o Consenso Clínico de Recomendações Nacionais em Crianças Traqueostomizadas da Academia Brasileira de Otorrinolaringologia Pediátrica (ABOPe) e Sociedade Brasileira de Pediatria (SBP) 2 . Porém, notou-se a invisibilidade da participação de enfermeiro na elaboração deste documento, um ator chave durante a internação e preparo para alta hospitalar.…”
unclassified